Gravity energy storage - Berrada, Asmae; Loudiyi, Khalid (Elsevier, 2019)
Gravity Energy Storage provides a comprehensive analysis of a novel energy storage system that is based on the working principle of well-established, pumped hydro energy storage, but that also recognizes the differences and benefits of the new gravity system. This book provides coverage of the development, feasibility, design, performance, operation, and economics associated with the implementation of such storage technology. In addition, a number of modeling approaches are proposed as a solution to various difficulties, such as proper sizing, application, value and optimal design of the system. The book includes both technical and economic aspects to guide the realization of this storage system in the right direction. Finally, political considerations and barriers are addressed to complement this work.